ANALISIS NUMERIK DALAM PENENTUAN KECEPATAN GERAK PENERJUN PAYUNG - Jimmy Lolowang (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
The mathematical model for paratrooper motion is formed based on Newton's Second Law where the change in momentum in a system is equal to the resultant force acting on it. This research is an experiment with analytical descriptive method, which aims to show which method is most effective for the root solution of the equation in determining the drag coefficient (c) of the parachutist's motion numerically using the graph method, the method for two, the false position method, the Newton- Raphson and the Secant method. Numerical analysis using Borland Delphi 7 program and data processing using Microsoft Excel program. The results showed that the graph method is only limited to determining the estimated value for the lower and upper limits that will be used in the method of the two-way method, the false position method, the Newton-Raphson method and the Secant method. It turns out that the Secant method is a more effective method in determining the drag coefficient (c) of the parachutist's motion, because there are only 4 iterations to obtain a c value of 16.8345.